Evaluation of the prophylactic efficacy of oral calcium gel in preventing milk fever relapse and hypocalcemia in post-calved dairy cows - Nagarjuna D; Bhagwat VG; Santhosh Kumar V (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Oral Calcium Gel (OCG) is a promising prophylactic and supportive supplement for milk fever and Downer syndrome in postcalved dairy cows. This study evaluated the efficacy of OCG supplementing in improving rumen motility, feed intake, parturition/calving, Retention of Placenta (ROP), and product performance and safety. A total of 30 postcalved dairy cows were randomly divided into three groups: G1, cows selected immediately after calving (n = 7); G2, cows with milk fever (n = 14); and G3, cows with milk fever and Downer syndrome (n = 9). The cows in G1 and G2 were supplemented with OCG 300 g; 8 - 12 h apart; repeat 2 - 4 supplementation for 1 - 2 days only. Conversely, the cows in G3 were supplemented with 300 g of OCG + IV calcium injection; + 8 - 12 h apart; repeat 1 - 3 supplementation of OCG (300 g). OCG supplementation improved rumen motility, feed intake, parturition/calving, and ROP in all three groups. The mean product performance and safety scores were also good. Notably, OCG supplementation was effective in preventing ROP, which is a common postpartum complication in dairy cows. Overall, the findings of this study suggest that OCG supplementation is a promising prophylactic and supportive agent for milk fever and Downer syndrome in postcalved dairy cows.